KARAKTERISTIK BIODEGRADABLE FILM BERBASIS SERAT SELULOSA ECENG GONDOK (Eichhornia Crassipes (Mart.) Solms) DENGAN PENAMBAHAN GLISEROL DAN CARBOXY METHYL CELLULOSE (CMC) CHARACTERISTICS OF BIODEGRADABLE FILM BASED ON CELLULOSE FIBER HYACINTH (Eichhornia Crassipes (Mart.) Solms) WITH ADDITION OF GLYCEROL AND CARBOXY METHYL CELLULOSE (CMC) - Renita Affanti; Zulferiyenni -; Fibra Nurainy; Sri Hidayati (Jurnal Agroindustri Berkelanjutan, 2024)
Hyacinth contains 60% cellulose which can be used as raw material for making biodegradable film. This study aims to determine the addition of glycerol and CMC concentrations to the biodegradable film characteristics of hyacinth cellulose fibers and to obtain the best treatment according to the Japanese Industrial Standard (JIS). This study was conducted with three repetitions and selected samples with the best visual appearance. The treatment consists of a combination of glycerol and CMC concentrations, namely P1 (0.5%:2%), P2 (0.5%:2.5%), P3 (0.5%:3%), P4 (1%:2%), P5 (1%:2.5%), P6 (1%:3%), P7 (1.5%:2%), P8 (1.5%:2.5%), P9 (1.5%:3%). Data collection is carried out triplo for parameters of tensile strength, percent elongation, thickness, and symplo for parameters of water vapor transmission rate (WVTR). Biodegradable film resistance test data at room temperature and biodegradability tests are presented in the form of drawings. The data of all parameters are analyzed and discussed descriptively. The addition of glycerol concentration increases tensile strength, percent elongation, and water vapor transmission rate (WVTR), and causes no tendency toward thickness. The addition of CMC concentration increases thickness, decreases tensile strength and water vapor transmission rate (WVTR), and causes no tendency towards percent elongation. The best results were obtained at P7 (1.5%:2%) for tensile strength parameters with values of 191.917 MPa, and at P3 (0.5%:3%) for thickness parameters and water vapor transmission rate (WVTR) with values of 0.172 and 3.438 g/m2/24 hours (WVTR). Biodegradable film decomposes in 21 days by biodegradability test.